2010
DOI: 10.1007/s10652-010-9203-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural design of a natural windbreak using computational and experimental modeling

Abstract: Computational and experimental approaches are employed for the structural design of a natural windbreak. It is intended to find the optimum tree shelterbelt to obviate the uneven wind speed distribution across the width dimension of a high-level competition rowing channel. The experimental results, obtained in a wind tunnel, and consisting of erosion-technique images and local wind-speed measurements, are used to benchmark the computational model. A good agreement between the two sets of results is obtained. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…As reported by Zeng et al [37], the abundant vertical structure of forests (e.g., species composition and configuration) also strengthens the resistance of individual tree stands to wind damage. us, our findings are different to that of Tamang et al [28] and Ferreira [38], who indicated that one or two rows of trees were optimal to reduce 85% of the wind speed and modify the micrometeorology.…”
Section: Linpan Micrometeorologycontrasting
confidence: 99%
“…As reported by Zeng et al [37], the abundant vertical structure of forests (e.g., species composition and configuration) also strengthens the resistance of individual tree stands to wind damage. us, our findings are different to that of Tamang et al [28] and Ferreira [38], who indicated that one or two rows of trees were optimal to reduce 85% of the wind speed and modify the micrometeorology.…”
Section: Linpan Micrometeorologycontrasting
confidence: 99%
“…In addition, the wind pressure can be increased by the dynamic effect of wind permeation, and Wilson [16] presented the drag coefficient according to 20~50% porosity and expressed the numerical value. Ferreira [17] constructed a poplar tree with a porosity of 87% at trunk level and 60% at the crown and measured the speed of the wind appearing on the backside. It was shown that wind speed appeared up to 1.6 times in the outskirts, but the average was 1.0.…”
Section: Wind Loadmentioning
confidence: 99%